Budget fraud reflected by statistical data from the regime change to nowadays (Academic Journal of Internal Affairs, 2020)
In the context of economic crime a completely new economic-social environment was formed during the mid-1990s in Hungary. The term white-collar crime has appeared, and the issue of interconnected VAT fraud strengthened. After joining the European Union, the practice of fiscal fraud related to acquisitions within the Community has evolved. These crimes included various VAT related frauds such as accepting pro forma invoices related to domestic sales activities and other economic activities related to acquisitions and sales within the Community. Whereas 180 adults were convicted for fiscal fraud in 2013; this figure has grown to 1637 adults and 2 juveniles by 2018. It is difficult to fight against white-collar crime. Crime prevention may therefore be necessary in order to fight off the number of frauds as well as diverting law enforcement agencies into the right direction regarding ongoing procedures.
Keywords: budget fraud; statistics; regime change